Modifikasi Metode Newton-Steffensen Tiga Langkah Menggunakan Interpolasi Kuadratik - Wartono Wartono; Eka Jumianti (UIN Sultan Syarif Kasim Riau, 2015)
The Newton-Steffensen’s method is iterative method that using for solving a nonlinear equationsresulting from the modification of the Steffensen’s method. In this paper, the author developed theNewton-Steffensen’s method written by Sharma [10] using by the quadratic interpolation. Based on thestudy results obtained the new iteration equation with six-order convergence that involving five evaluationfunctions with efficiency index 1,43097. Besides, numerical simulations performed on some functions withdifferent initial guess value and obtained that performance of the new method is better than the Newton’smethod, Steffensen’s method and Newton-Steffensen’s method.Keywords: efficiency index, Newton-Steffensen method, orde of convergence, nonlinear equation